2020
DOI: 10.1177/1010428320918050
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of HOX genes to cancer hallmarks: Enrichment pathway analysis and review

Abstract: Homeobox genes function as master regulatory transcription factors during development, and their expression is often altered in cancer. The HOX gene family was initially studied intensively to understand how the expression of each gene was involved in forming axial patterns and shaping the body plan during embryogenesis. More recent investigations have discovered that HOX genes can also play an important role in cancer. The literature has shown that the expression of HOX genes may be increased or decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 165 publications
(215 reference statements)
0
36
0
Order By: Relevance
“…The family consists mainly of HOX genes, which are master regulatory transcription factors in embryogenesis, cellular development, and issue homeostasis (Li B. et al, 2019 ). Recent researches have shown that depending on the type of the tumor, the expression of HOX genes may be increased or decreased and play roles in oncogenesis or tumor suppression (Shah and Sukumar, 2010 ; Bhatlekar et al, 2014 ; Brotto et al, 2020 ). (5) Keratin-associated proteins have no confirmed role in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The family consists mainly of HOX genes, which are master regulatory transcription factors in embryogenesis, cellular development, and issue homeostasis (Li B. et al, 2019 ). Recent researches have shown that depending on the type of the tumor, the expression of HOX genes may be increased or decreased and play roles in oncogenesis or tumor suppression (Shah and Sukumar, 2010 ; Bhatlekar et al, 2014 ; Brotto et al, 2020 ). (5) Keratin-associated proteins have no confirmed role in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…More recent investigations have discovered that HOXA9 can act as both an oncogene and a tumour suppressor gene in a context-dependent manner. 25 The literature has shown that the expression of HOX genes may be increased or decreased in different tumors and that these alterations may differ depending on the specific HOX gene involved and the type of cancer being investigated. 25 , 26 However, conditions under which it assumes either role remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the HOX network consists of 39 genes that exhibit a high degree of sequence similarity, particularly in the homeobox domain. Homeobox genes function as master regulatory transcription factors during development, and their expression is often altered in cancer (Brotto et al, 2020;Li et al, 2020;Qu et al, 2019). Many of the chromosomal translocations associated with acute leukemias involve HOX genes, such as mixed lineage leukemia, which leads to the inappropriate expression of specific HOX gene subsets (Collins & Thompson, 2018;Dickson, Lappin & Thompson, 2009).…”
Section: Overview Of Mrgsmentioning
confidence: 99%